A key to the Neotropical species of the Enicospilus ramidulus species-group (Hymenoptera: Ichneumonidae: Ophioninae), with the description of a new Brazilian species - Lima, Alessandro Rodrigues; Jacobi, Claudia Maria; Kumagai, Alice Fumi (Zootaxa, 2012)
A key to the Neotropical species of the Enicospilus ramidulus species-group is provided, with the exception of GalápagosIslands species. A total of 22 specimens of E. purgatus (Say) were examined and its known distribution (Southern Brazil)extended to the states of Bahia and Amazonas, in Northeastern and Northern Brazil, respectively. A new species, Enicospilus diae Lima & Kumagai sp. n., is described from Southeastern Brazil.